Smart Manufacturing of Electric Vehicles - TUNABOYLU, BAHADIR (Springer Science and Business Media Deutschland GmbH, 2021)
The future of the manufacturing sector is evolving with the Industry 4.0, and its repercussions are felt in the factory, the business, product launch and also impacts customer aspects in the overall cycle. These technological innovations create opportunities for new disruptive entries to the market, for instance in automotive manufacturing. It is well known that the automotive industry is under the control of large OEMs since the very beginning. It is very difficult to compete as a newcomer because the production process of the Internal Combustion Engine (ICE) and the chassis require high technology, investment, and a well-defined supply chain that create a monopolistic environment for the sector. Therefore, we propose a microfactory concept as a novel manufacturing method that allows a quicker entry for new players in the automotive industry especially for electric vehicles (EVs). The microfactory described in this paper, presents an alternative solution to overcome the existing monopolies with the electric motor, a tubular chassis allows for lean manufacturing, and a novel supply chain model. Digital transformation shows itself in production systems by Industry 4.0 applications and more recently in the blockchain-based supply chain applications are being investigated. Further, a detailed cost analysis to compare conventional car manufacturing and microfactory concept EV manufacturing are presented. In addition, the blockchain technology is proposed to improve the supply chain of EV manufacturing. This study indicates that the microfactory provides flexible and customized production of urban electric vehicles minimizing both ecological footprint and total investment. © 2021, The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG.
Keywords: Advanced manufacturing technology; Automotive industry; Electric vehicles; Flexible manufacturing; Sustainable production; Sustainable supply chain